A JEWISH THEOLOGY OF RESURRECTION. - GOTTLIEB, MARK (First Things: A Monthly Journal of Religion & Public Life, 2023)
The article focuses on the theological perspective of Pinchas Lapide, a 20th-century Orthodox Israeli scholar, regarding the resurrection of Jesus and its implications for Judaism and Christianity. Topics discussed include Lapide's argument for the historicity of the resurrection, its role in the spread of Christianity, and the potential for fostering interreligious understanding and cooperation between Jews and Christians.